The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1063/1.4947286
|View full text |Cite
|
Sign up to set email alerts
|

Rashba splitting of 100 meV in Au-intercalated graphene on SiC

Abstract: Intercalation of Au can produce giant Rashba-type spin-orbit splittings in graphene but this has not yet been achieved on a semiconductor substrate. For graphene/SiC(0001), Au intercalation yields two phases with different doping. Here, we report the preparation of an almost pure p-type graphene phase after Au intercalation. We observe a 100 meV Rashba-type spin-orbit splitting at 0.9 eV binding energy. We show that this giant splitting is due to hybridization and much more limited in energy and momentum space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…No π * band is observed. These observations are reminiscent of others made with related systems [15,17,18,50,21,22], and suggest that graphene here has a freestanding character. In contrast, ARPES measurements on graphene/Re(0001) in the absence of the Au intercalant suggest strong electron donation from the substrate to graphene and hybridization between the C and Re orbitals (figure S1(d)), consistent with previous reports [15,16].…”
Section: Dirac Cone Of Quasi Free-standing Graphenesupporting
confidence: 83%
“…No π * band is observed. These observations are reminiscent of others made with related systems [15,17,18,50,21,22], and suggest that graphene here has a freestanding character. In contrast, ARPES measurements on graphene/Re(0001) in the absence of the Au intercalant suggest strong electron donation from the substrate to graphene and hybridization between the C and Re orbitals (figure S1(d)), consistent with previous reports [15,16].…”
Section: Dirac Cone Of Quasi Free-standing Graphenesupporting
confidence: 83%
“…We as well observe the Rashba splitting at about −1 eV due to the interaction between the graphene and gold bands, as reported in ref. 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The effects reported were doping of the graphene π-bands 30,31 or mini-gaps opening in the graphene Dirac cone due to moiré superperiodicity 32 . It was recently shown that the interaction between the 5d orbitals of gold and the valence band of graphene can open a spin-orbit gap deep in the valence band of goldintercalated graphene on SiC(0001) 33 . However, no evidence of two-dimensional dispersing bands stemming from the metal layer was ever reported, which would be indicative of a well-defined order of the film.…”
mentioning
confidence: 99%
“…bringing atomic layers on or between graphene and the substrate. For example the charge carrier concentration was successfully changed by different layer thicknesses of Germanium and Au‐intercalation was shown to lead to a Rashba‐type spin‐orbit splitting . Bilayer graphene intercalated with calcium showed superconducting behavior at 4 K and further evidence for superconductivity in Li‐decorated monolayer graphene was reported .…”
Section: Discussionmentioning
confidence: 96%